Factors Influencing Utilization of Sexual and Reproductive Health Services Among Secondary School Adolescents in Ibadan, Nigeria - Adeyanju, Olufunmilayo Dorcas; Ndikom, Chizoma Millicent; Akinwaare, Margaret Omowaleola (British Journal of Healthcare and Medical Research, 2024)
Purpose: The aim of this study was to assess factors influencing utilization of Adolescents Sexual and Reproductive Health Services (ASRHS) in Ibadan, Nigeria. Methods: Descriptive cross-sectional design was used. Multi-stage sampling was adopted in selecting 391 adolescents out of 2943 from four selected schools in 2 Local Government Areas (LGAs) of Ibadan. Semi-structured questionnaire used to collect data from the adolescents. Perceived factors influencing accessibility and utilization of ASRHS under personal, socio-economic and institutional domains were tested using binary regression. A calculated p-value greater than 0.05 statistical significance was considered to have no influence at a confidence interval of 95%. Results: The mean age of respondents was 16.6.4 ± 1.2 years. The majority were females, 219(57.0%). Most 377(97.4%) were singles, 280(72.4%) were in Art while 90(23.2%) in Science discipline. Bivariate analysis revealed young age (X2 = 9.90; p = 0.002), gender inequity (X2 = 5.645; p = 0.018), persuasion from a friend (X2 = 16.557; p < 0.001), persuasion from parents (X2 = 11.698; p = 0.001), meeting other youths (X2 = 10.460; p = 0.001), the attitude of service provider (X2 = 9.061; p = 0.003) and distance of service location (X2 = 4.847; p = 0.028) were significantly associated with utilization of ASRHS. At the multivariate level, gender inequity (Adjusted OR=5.35(2.11 - 13.53); X2=10.16) and attitude of service provider (Adjusted OR= 0.39(0.19 - 0.80) were significantly associated with utilization of SRH services. Discussion: The predictive factors of gender (socio-economic factor) and attitude of SRH providers (institutional-based factor) in utilization of ASRHS indicates poor integration of ASRHS across the PHCs in the setting of the study. Thus, the need to address the lack of or poor adolescent-friendly sexual and reproductive health (ASRH) services in health facilities in the setting of the study, in particular and across Nigeria, in general becomes eminent.